2012
DOI: 10.1371/journal.pone.0042016
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regional Homogeneity in the Development of Minimal Hepatic Encephalopathy: A Resting-State Functional MRI Study

Abstract: BackgroundLittle is known about how spontaneous brain activity progresses from non-hepatic encephalopathy (non-HE) to minimal HE (MHE). The purpose of this study was to evaluate the evolution pattern of spontaneous brain activities in cirrhotic patients using resting-state fMRI with a regional homogeneity (ReHo) method.Methodology/Principal FindingsResting-state fMRI data were acquired in 47 cirrhotic patients (minimal HE [MHE], n = 20, and non-HE, n = 27) and 25 age-and sex-matched healthy controls. The Kenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 33 publications
8
42
0
Order By: Relevance
“…The pattern of resting-state brain activities obtained by the ReHo method is very similar to that observed by PET in healthy individuals, which indicates that ReHo is a promising measurement for the resting-state local brain activities [18]. ReHo has been successfully applied to study a variety of neurological and psychiatric diseases, such as epilepsy [20], social anxiety disorder [21], major depression [22], Parkinson's Disease [23], hepatic encephalopathy [24], and Alzheimer's disease [25]. To the best of our knowledge, there has been no report on the neural mechanism of cognitive function impairments in ESRD patients using rs-fMRI with ReHo algorithm.…”
Section: Introductionsupporting
confidence: 53%
“…The pattern of resting-state brain activities obtained by the ReHo method is very similar to that observed by PET in healthy individuals, which indicates that ReHo is a promising measurement for the resting-state local brain activities [18]. ReHo has been successfully applied to study a variety of neurological and psychiatric diseases, such as epilepsy [20], social anxiety disorder [21], major depression [22], Parkinson's Disease [23], hepatic encephalopathy [24], and Alzheimer's disease [25]. To the best of our knowledge, there has been no report on the neural mechanism of cognitive function impairments in ESRD patients using rs-fMRI with ReHo algorithm.…”
Section: Introductionsupporting
confidence: 53%
“…This finding indicates decreased neuronal activity in those regions led by reduced cerebral oxygen consumption and cerebral blood flow (31). Previous MHE studies showed decreased regional homogeneity in the cuneus and precuneus (11,12) and weakened functional connectivity among the default mode network (14,15) suggesting an abnormal connection among these regions. As members of the default mode network, the precuneus and MPFC are responsible for cognition.…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless, questions to address in a longitudinal study are clearly raised here. Resample voxel size was set as 3 mm × 3 mm × 3 mm, which is a very common resampling voxel size for ReHo analysis (Chen et al, 2015; Ni et al, 2012; Ping et al, 2013). In this study, its original voxel size was 3.75 mm × 3.75 mm × 4 mm.…”
Section: Discussionmentioning
confidence: 99%